Analysis of intersectoral intervention in preventing sexual violence in early childhood (Research, Society and Development, 2021)
The respective article presents the result of the analysis of the interventional practice of the Specialized Reference Center for Social Assistance (CREAS) of São José dos Pinhais/PR in intersectoral action in the prevention of sexual violence in early childhood. The objective is to evaluate the project to prevent child sexual violence, considering the analysis of the professionals who participated in the training process. The intervention was carried out through a training project for professionals in the education network in order to provide content and clarification on sexual abuse in early childhood and to support instrumental treatments necessary to prevent violence against children and their parents. school setting. Through the qualitative analysis carried out with data extracted from questionnaires applied in the training, this study pointed out the relevance of intersectoral work in preventing situations of sexual violence in early childhood, a multidimensional phenomenon, as well as its consequences.